Understanding broadband under-utilization in Japan - Maria Bourna; Hitoshi Mitomo (International Telecommunications Society (ITS), 2014)
Improved internet connectivity has been a consistent aim of Japanese telecommunications policy in the past decades, however, despite the high availability of high speed and ultra-high speed broadband services, actual use has yet to match network capacity. This study hopes to explore this paradox by looking at the factors that affect demand for broadband services. To achieve this, the relationship between overall broadband adoption and two basic demand factors, namely price of internet services and presence of a competitor in the form of wireless broadband, was examined over a 12-year period. The findings suggest that the lag in adoption can be attributed to both a higher demand for wireless connectivity and high broadband contract prices, while network effects may play a positive role in diffusion. Given that Japanese broadband policy has tended to focus more on the role of price as a mechanism for improving penetration, this study ultimately contributes to the discussion of policy efficiency by providing some empirical basis for the consideration of alternative demand-side incentives.
Keywords: 330; broadband adoption; Japan; mobile internet